Trends of Cochineal (Dactylopius coccus) Infestation as Affected by Armed Conflict, and Intervention Mechanisms for Sustainable Management in Tigray, Northern Ethiopia - Haftay Gebreyesus Gebreziher; Simon Zebelo; Yohannes Gerezihier Gebremedhin; Gebremedhin Welu Teklu; Yemane Kahsay Berhe; Daniel Hagos Berhe; Araya Kahsay Gerezgiher; Araya Kiros Weldetnsae; Zinabu Hailu; Gebrekidan Tesfay Weldeslasse; Gebremariam Gebrezgabher Gebremedhin; Tsegay Kahsay Gebrekidan; et al. (Plants)
The cactus pear (Opuntia ficus-indica) is a crucial plant in Tigray, northern Ethiopia, widely distributed in arid and semi-arid environments. It serves as a seasonal food, and is used in livestock feed, fencing, soil conservation, and environmental protection. Recently, the cactus pear populations in Tigray have been severely affected by an exotic insect, the cochineal (Dactylopius coccus). It damaged cactus pear populations in the region’s southern, southeastern, and eastern zones. The Tigray war that broke out in November 2020 exacerbated D. coccus infestation. A study was conducted in the eastern zone of Tigray to assess the impact of the armed conflict on the trends of this infestation and propose sustainable management approaches for sustainable cactus pear production in post-war Tigray. Both primary and secondary data were collected and analyzed. The findings revealed that D. coccus infestation significantly increased during the war and in the post-war period, compared to in the pre-war period. The number of districts involved and level of D. coccus infestation of cactus pear populations increased. The rapid spread was attributed to the interruption of pest management activities due to the armed conflict. To mitigate the spread and ensure sustainable cactus pear production, this study recommends different management approaches to manage D. coccus dissemination and sustainably produce cactus pear in the region, including pest prevention, suppression, or eradication.